Studies of Properties of Liquids by Ultrasonic Method - P. Tadkalkar, Alka; P. Pawar, Pravina; K. Bichile, Govind (Asian Journal of Chemistry, 2012)
Ultrasonic study and transport properties of pure and mixed liquids are useful to study interactions in solutions. The thermodynamic parameters such as density, viscosity, adiabatic compressibility, acoustic impedance, intermolecular free length, relative association and hydration number have been discussed. These parameters are further used to study molecular interactions in solution.